Investigación de la acción de los nitratos y nitritos contenidos en algunos vegetales como causantes de metahemoglobinemia - Anaya Pajuelo, Rosalía (1999)
The major acute toxic effect of nitrate and nitrite poisoning is methaemoglobinemia.Methaemoglobin reduces the oxygen-carrying capacity of the blood and in addition, it shifts the oxyhaemoglobin dissociation curve to the leftinterferin with the unloading of oxygen.Hypotension and collapse may also occur.The principal concem with exposure to nitrate is its biological reduction to reactive and toxic nitrite.The major use of nitrate is as lertilizer. It is also used in the manufacture of nitrites, nitrous oxide, explosives, pyrotechnics, matches and preserving additive to food.Nitrite es used as a food preservative and colouring agent, e.g. curing 0f meat, in the manufacture of diazo dyes, in the textile industry and in photography.The concentrations of nitrates and nitrites in different vegetable species that supposedly cause methahaemoglobin, being a problematic average concentration of nitrates in: beet 2,139 ppm; turnip 2,038 ppm; spinach 1,195 ppm; medic 66 ppm; carrot 404 ppm were determined by Gas - Liquid Chromatogrephy (GLC).The symptoms of the methehaemoglobin were evaluated experimentally in dogs administering different dose of solution of sodium nitrite. Later on, the methahaemoglobin was quantified by the spectrophotometric method observed thet the dose of 50 mg/kg of weight produced 78% of methaheemoglobin in vivo.